Genome-Wide Analysis of the Gene Structure, Expression and Protein Interactions of the Peach (Prunus persica) TIFY Gene Family - Sheng, Yu; Yu, Hong; Pan, Haifa; Qiu, Keli; Xie, Qingmei; Chen, Hongli; Fu, Songling; Zhang, Jinyun; Zhou, Hui (Frontiers in Plant Science, 2022)
The TIFY family is a plant-specific gene family involved in regulating many plant processes, such as development and growth, defense and stress responses, fertility and reproduction, and the biosynthesis of secondary metabolites. The v2.0 peach (Prunus persica) genome, which has an improved chromosome-scale assembly and contiguity, has recently been released, but a genome-wide investigation of the peach TIFY family is lacking. In this study, 16 TIFY family genes from the peach genome were identified according to the peach reference genome sequence information and further validated by cloning sequencing. The synteny, phylogenetics, location, structure, and conserved domains and motifs of these genes were analyzed, and finally, the peach TIFY family was characterized into 9 JAZ, 1 TIFY, 1 PPD and 5 ZML subfamily members. Expression profiles of peach JAZ, PPD, and ZML genes in various organs and fruit developmental stages were analyzed, and they showed limited effects with fruit ripening cues. Four TIFY members were significantly affected at the mRNA level by exogenous treatment with MeJA in the peach epicarp, and among them, PpJAZ1, PpJAZ4 and PpJAZ5 were significantly correlated with fruit epicarp pigmentation. In addition, the TIFY family member protein interaction networks established by the yeast two-hybrid (Y2H) assay not only showed similar JAZ-MYC2 and JAZ homo- and heterodimer patterns as those found in Arabidopsis but also extended the JAZ dimer network to ZML-ZML and JAZ-ZML interactions. The PpJAZ3-PpZML4 interaction found in this study suggests the potential formation of the ZML-JAZ-MYC complex in the JA-signaling pathway, which may extend our knowledge of this gene family’s functions in diverse biological processes.